PENDIDIKAN SEKS BAGI REMAJA DALAM PERSPEKTIF HUKUM ISLAM - Muhammad Sudirman (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2015)
Sex education is teaching efforts, awareness, and information about sexual problems are given to children since he understands the problems relating to sex, instinct, and marriage. And sex education for adolescents is important, it is intended to menhindarkan teenagers from acts of adultery is forbidden by Islam. The main role in sex education for adolescents held by the parents, because the parents are responsible for the development of their children so as not to fall into the hole contempt. As for sex education can be done in several ways that are global is to give sense to the child sex as well as provide an understanding of the limitations in the mix, and increasing faith in Allah swt children.